Natural Products as Novel Therapeutic Agents for Triple-Negative Breast Cancer: Current Evidence, Mechanisms, Challenges, and Opportunities - Qingzhou Li; Zhen Ye; Guilin Wang; Yuhui Chen; Jinghong Deng; Dong Wang; Yumei Wang (Molecules)
Breast cancer (BC) tops the list of causes for female fatalities globally, with the elusive triple-negative breast cancer (TNBC) constituting 10–20% of all cases. Current clinical strategies for combating TNBC encompass a multifaceted approach, including surgical intervention, radiation therapy, chemotherapy, and advanced targeted drugs and immunotherapies. While these modalities have catalyzed significant advancements in TNBC management, lingering limitations continue to pose formidable challenges. There is an acute need for novel therapeutics in the realm of TNBC treatment. Natural products (NPs) have emerged as a rich reservoir for pharmaceutical innovation, owing to their extraordinary range of structures and physicochemical properties. Scholars have reported diverse evidence of NPs’ efficacy against TNBC. This review aims to comprehensively explore the bioactive constituents, specifics and commonalities of chemical structure, and pharmacological mechanisms of NPs, specifically examining their multifaceted roles in impeding TNBC. NPs, which have recently garnered significant interest, are intriguing in terms of their capacity to combat TNBC through multifaceted mechanisms, including the suppression of tumor cell proliferation, the induction of apoptosis, and the inhibition of tumor metastasis. These natural agents primarily encompass a range of compounds, including terpenoids, glycosides, phenolic compounds, and alkaloids. An in-depth exploration has unveiled their involvement in key signaling pathways, including the transforming growth factor-beta (TGF-β), vascular endothelial growth factor A (VEGFA), phosphoinositide 3-kinase/protein kinase B (PI3K/AKT), Wingless/Int-1 (Wnt) /β-catenin, and mitogen-activated protein kinase (MAPK) pathways. Meanwhile, this review also looks at the challenges and opportunities that arise from harnessing natural compounds to influence TNBC, while outlining the prospective trajectory for future research in the field of NPs.